Enduring Acequias : Wisdom of the Land, Knowledge of the Water - Arellano, Juan Estevan (Book collections on Project MUSE., 2014)
Touching on the Middle East, Europe, Mexico, and South America before circling back to New Mexico, Arellano makes a case for preserving the acequia irrigation system and calls for a future that respects the ecological limitations of the land.